Self-medication practice among undergraduate medical students in government medical college of Andhra Pradesh - Yadav, Preeti K.; Deep, Kolanu Nikhil; Karthiga, Vasudevan; Shrivatsam, Paidi; Velaga, Lakshmi Chandana; Chand, Purna (International Journal Of Community Medicine And Public Health, 2024)
Background: Self-medication involves using medicines without professional advice, a common global practice due to limited healthcare access, over-the-counter drug availability, and widespread internet use. Medical students, despite lacking prescription authority, often self-medicate due to their drug knowledge. Methods: This cross-sectional study was conducted in June 2024 among undergraduate medical students at Government Medical College, Srikakulam. Data on socio-demographics and knowledge, attitudes, and practices (KAP) regarding self-medication were collected through a validated online questionnaire, with 520 completed responses from 623 students. Results: The prevalence of self-medication was 67%. Most respondents were male (61%) and 2nd-year students (32.5%). Self-medication was common for minor illnesses (76%), with antacids (83%) and analgesics (74%) being the most used drugs. Although 70.2% acknowledged the risks of self-medication, its prevalence increased with semester progression, peaking at 96% among 4th-year students. Conclusions: Self-medication is widespread among medical students, driven by easy drug access and textbook knowledge. The study underscores the need for better education on the risks and stricter drug dispensing regulations to mitigate health risks.